The Analysis Of Income And Welfare level Of Dairy Cattle Breeder (Case Study In KUD KarangplosoBocek Village Malang Districts) - Marselina Wea Wula, Dimas Pratidina Puriastuti, Waluyo Edi Susanto (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2016)
ABSTRAK The research knows the income and the welfare level of dairy cattle breeder. The research was done from August〖22〗^th – November 〖22〗^th,2016. Survey was conducted at KUD Karangploso. With questionnaire given to 40 respondent.Respondent where dairyfarmer of KUD Karangploso members. The data were analyzed using the descriptive analyzed the result showed that. The average income dairy farmers based on a fixed cost Rp 970.000 and variable cost Rp 1.673.000.analysisthe income profits analysis Rp 882.000. cows lactation and value r/c is 1,33.The welfare level of dairy cattle breeder measures based on an indicator line of poverty central bureau of statistics is 90% a member of KUD.The economic benefits of cooperatives welfare obtained consisting of economic benefits cooperatives indirectly Rp 372.000 and economic benefits cooperatives directlyRp 215.000 so the overall economic benefits cooperatives Rp 587.000 Conclusions from research advantage of the income to maintain 1 cows lactation Rp.882.000. The ratio of value over cost is 1,33.Total economic benefits cooperatives is Rp.587.000 . Keywords :Revenue,Cost,LevelHousuhold Welfare.